2017
DOI: 10.2460/ajvr.78.2.195
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary evaluation of the effects of photobiomodulation therapy and physical rehabilitation on early postoperative recovery of dogs undergoing hemilaminectomy for treatment of thoracolumbar intervertebral disk disease

Abstract: OBJECTIVE To evaluate the effects of postoperative photobiomodulation therapy and physical rehabilitation on early recovery variables for dogs after hemilaminectomy for treatment of intervertebral disk disease. ANIMALS 32 nonambulatory client-owned dogs. PROCEDURES Dogs received standard postoperative care with photobiomodulation therapy (n = 11), physical rehabilitation with sham photobiomodulation treatment (11), or sham photobiomodulation treatment only (10) after surgery. Neurologic status at admission, di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
52
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(62 citation statements)
references
References 62 publications
8
52
1
1
Order By: Relevance
“…The results of our study are in agreement with results from a recent randomized, blinded clinical trial on the efficacy of immediate postoperative laser treatment and rehabilitation in dogs after surgery for TL‐IVDH . This trial included paraplegic, pain perception negative dogs as well as the dogs included in our trial, but like ours, did not find any difference in recovery time and outcome among dogs in the different treatment groups.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The results of our study are in agreement with results from a recent randomized, blinded clinical trial on the efficacy of immediate postoperative laser treatment and rehabilitation in dogs after surgery for TL‐IVDH . This trial included paraplegic, pain perception negative dogs as well as the dogs included in our trial, but like ours, did not find any difference in recovery time and outcome among dogs in the different treatment groups.…”
Section: Discussionsupporting
confidence: 91%
“…Recommendations on postoperative rehabilitation range from advising against it, to implementing multimodal rehabilitation programs . Objective evidence for the role of rehabilitation in dogs after surgical treatment of TL‐IVDH is sparse, and evidence available is somewhat contradictory with retrospective studies suggesting benefit and a recent, randomized, controlled (RCT) clinical trial failing to demonstrate an effect …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Photobiomodulation applied to adult rats that underwent T9 dorsal hemisection resulted in significantly increased axonal number and distance of regrowth [26]. However, recent studies in dogs have published contrasting results on the effects of laser therapy on postoperative IVDH; thus the literature lacks clear evidence-based advantages [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…The use of physical therapy in veterinary medicine is gradually increasing in the last decade and several studies described its role in the outcome of dogs with thoracolumbar (TL) intervertebral disk herniation (IVDH) [1][2][3][4][5][6]. In cats, many studies were performed under experimental conditions and showed the usefulness of treadmill activity in promoting recovery of motor function in cats after incomplete and complete spinal cord lesions [7][8][9].…”
Section: Introductionmentioning
confidence: 99%